1998
DOI: 10.3354/ame014281
|View full text |Cite
|
Sign up to set email alerts
|

Microzooplankton grazing in the Estuary of Mundaka, Spain, and its impact on phytoplankton distribution along the salinity gradient

Abstract: Microzooplankton grazing impact (<200 pm fraction) on phytoplankton along a salinity gradient in the Estuary of Mundaka (Bay of Biscay, Spain) was analyzed dunng summer (August 1990) using a serial dilution method. Both microzooplankton grazing rate and phytoplankton growth rate were high (mean g = 0.75 d-l, mean k = 1.90 d-' respectively), and well correlated, denoting an optimization in the efficiency of energy transport through the pelagic food web. Microzooplankton herbivory represented a mean loss of 38% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…Studies of the in situ grazing of E. affinis in the Gironde Estuary have shown that the concentration of suspended particulate matter had no effect on phytoplankton ingestion in this species (Irigoien et al 1993). Several studies which support our hypothesis have shown that microzooplankton herbivory represents from 50 to 80% of potential phytoplankton primary production and is an important sink for estuarine phytoplankton production (McManus & Ederington 1992, Froneman & McQuaid 1997, Ruiz et al 1998, Lehrter et al 1999.…”
Section: Effect Of Grazingsupporting
confidence: 70%
“…Studies of the in situ grazing of E. affinis in the Gironde Estuary have shown that the concentration of suspended particulate matter had no effect on phytoplankton ingestion in this species (Irigoien et al 1993). Several studies which support our hypothesis have shown that microzooplankton herbivory represents from 50 to 80% of potential phytoplankton primary production and is an important sink for estuarine phytoplankton production (McManus & Ederington 1992, Froneman & McQuaid 1997, Ruiz et al 1998, Lehrter et al 1999.…”
Section: Effect Of Grazingsupporting
confidence: 70%
“…Caron 2001). In the present work, as in previous studies of herbivory rates in the Urdaibai estuary (Cotano et al 1998, Ruiz et al 1998, no nutrients were added, because phytoplankton are not nutrient limited, at least in the upper zone of the estuary. Some nutrient limitation may occur in the lower estuary, but we decided not to add nutrients to avoid introducing other uncertainties.…”
Section: Methods For Measuring Bacterivory and Herbivorymentioning
confidence: 79%
“…3 dilution fractions (Gallegos 1989). As in previous measurements of herbivory rates in the Urdaibai estuary, no nutrients were added (see Cotano et al 1998, Ruiz et al 1998). The biomass of chl a and the percentage standing stock of phytoplankton consumed daily were estimated as in Boissonneault-Cellineri et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…3, there is no apparent trend for the transformed m : ratios as a function of initial concentration of Chl a. At the very high end of the chlorophyll values, the data are dominated by a single study (Ruiz et al 1998;Mundaka Estuary). These are plotted at 62 g Chl a L Ϫ1 , the mean chlorophyll estimate, because concentrations were not reported for individual experiments.…”
Section: Resultsmentioning
confidence: 92%